Kutu Sisik pada Tanaman Apel di Kecamatan Bumiaji, Kota Batu - Sama' Iradat Tito; Nurul Jadid Mubarakati; Ari Hayati (Institut Pertanian Bogor, 2024)
Scale lice have attacked apple fields in 8 villages in Bumiaji District, Batu City, namely Giripurno, Tulungrejo, Pandanrejo, Sumbergondo, Bulukerto, Punten, Gunungsari, and Bumiaji villages since 2005. Knowledge of the biological aspects of this pest can be done using sticky bands. This is aimed at controlling pests. Determination of sample plants was carried out systematically as many as 18 sample plants on manalagi apple (Malus sylvestris). The sample plants were apple plants that were attacked by scale lice. The type of adhesive treatment was adjusted to the variation of position (east, west, central) and research height (1m and 1.5m). The results obtained were that the pest found was Diaspidiotus perniciosus and the natural enemy found was Encarsia strenua. The part that has the most attacks is the stem/twig. The eastern branch with a height of 1.5 m has a higher even distribution of scale lice than the other parts. The highest dominance index (C) of scale lice of 0.29 was obtained by the middle-adhesive treatment of height 1m or rootstock. The pattern of population distribution based on sticky bands is random and tends to be individualistic. Keywords: apple plant, diaspididae, scale lice